Rural population in Ukraine: assessing reality, looking for revitalization - Skryzhevska, Yelizaveta; Karácsonyi, Dávid (Hungarian Geographical Bulletin, 2012)
The rural population in Ukraine has declined dramatically since 1989. Today, Ukraine’s rural areas suffer from depopulation and out-migration as well as from the low fertility, high mortality, and declining life expectancy of residents, which are the obvious indications of a demographic crisis. To reverse these negative demographic trends, governmental policies should be directed at improving economic and social well-being in rural areas. This study attempts to describe and analyze the major trends and regional variations in Ukraine’s rural population decline, to bring into focus the problems of rural areas that are affected by the demographic crisis, and to provide recommendations for the rural development policy-makers that would help revitalize rural areas.